2019
DOI: 10.1101/808279
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional Profiling of Primate Central Nucleus of the Amygdala Neurons to Understand the Molecular Underpinnings of Early Life Anxious Temperament

Abstract: ContributionsRK, ASF, JAO, PHR and NHK conceptualized the study. NHK and ASF oversaw the study. RK, MKR, and EMF collected behavioral data. RK and DAF developed the rapid staining laser-capture microdissection (LCM) microscopy method and collected the RNA data. DAF performed RNA extractions. JAK and his group performed RNA-Seq. TS aligned the RNA-Seq data. RK and TS analyzed the RNA-Seq data. RK, MKR, and PHR collected tissue and PHR assessed cortisol. JLF, NHK, and RK conceptualized the stereology study. RK a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 100 publications
3
4
0
Order By: Relevance
“…That said, together with findings in humans, these data contribute to the rationale for further study of CTNNA2 in anxiety-related behavior in animal models, and highlight a potential molecular mechanism that may drive stable anxiety across the lifespan. More generally, our results are consistent with many molecules contributing to IT, reflecting disruption across many of the brain regions and cell-types that are thought to play a role in anxiety and threat-processing (See supplemental discussion) (31,33,34,47,48,54).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…That said, together with findings in humans, these data contribute to the rationale for further study of CTNNA2 in anxiety-related behavior in animal models, and highlight a potential molecular mechanism that may drive stable anxiety across the lifespan. More generally, our results are consistent with many molecules contributing to IT, reflecting disruption across many of the brain regions and cell-types that are thought to play a role in anxiety and threat-processing (See supplemental discussion) (31,33,34,47,48,54).…”
Section: Discussionsupporting
confidence: 79%
“…In addition to our genome-wide significant hit in CTNNA2, we relaxed the formal genome-wide significance threshold and explored variation in other genes that were marginally significantly (p<.01) associated with IT (Table S4), but do not reach genome-wide significance. Interestingly, our results revealed uncorrected associations with genetic variation in genes we've previously implicated in inhibition, including an 3' UTR variant in NTRK3 (p=0.005) and an intronic variant in PRKCD (p=.007) (33,34,54). Such associations must be considered less meaningful but can provide indications of genetic effects that deserve further study.…”
Section: Study 3: Gwas Of Itmentioning
confidence: 66%
“…In addition to our genome-wide significant hit in CTNNA2 , we relaxed the formal genome-wide significance threshold and explored variation in other genes that were marginally significantly (p<.01) associated with IT ( Table S4 ), but do not reach genome-wide significance. Interestingly, our results revealed uncorrected associations with genetic variation in genes we've previously implicated in inhibition, including an 3' UTR variant in NTRK3 (p=0.005) and an intronic variant in PRKCD (p=.007) ( 31 , 33 , 53 ). Such associations must be considered less meaningful but can provide indications of genetic effects that deserve further study.…”
Section: Resultsmentioning
confidence: 62%
“…The CeL sends robust projections to the laterodorsal BST (BSTLd) and this pathway is important in threat responses. In our study, 5 we found that about half of PKCd neurons project to the BSTLd, whereas very few SST neurons project to the BSTLd. We also noted dense SST varicosities surrounding BSTLd-projecting PKCd neurons, suggesting that SST may modulate this pathway.…”
Section: Commentarysupporting
confidence: 45%
“…The CeL coordinates threat responses by integrating threatrelevant information and modulating the CeM's output though a GABAergic microcircuit comprised of neuronal subpopulations e.g., protein kinase C type delta (gene: PRKCD, protein: PKCd) and somatostatin (gene: SST, protein: SST) neurons. 4 In our recently published study, 5 we describe our efforts to understand Ce gene expression in relation to individual differences in AT. Among our top hits was PRKCD, a marker of a CeL neuronal subpopulation that is critical for threat responses.…”
Section: Commentarymentioning
confidence: 99%